2020
DOI: 10.4251/wjgo.v12.i10.1146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic factors in different age groups and prognostic significance of neutrophil-lymphocyte ratio in patients with gastric cancer

Abstract: BACKGROUND Gastric cancer (GC) is one of the most common malignant tumors in the world. Although in recent years tremendous progress has been made in its early detection, the postoperative overall survival (OS) of GC patients remains extremely low. A number of studies have shown that age, to varying degrees, affects the prognosis of patients with GC. Therefore, this study retrospectively analyzed the clinical and pathologic data of patients with GC to explore the differences in the clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“… 3 Higher PLR and NLR have been associated with poor survival in GC. 4 , 5 However, only a few studies have compared the effectiveness of multiple inflammatory response markers for predicting survival outcomes. In the current study, we identified the most suitable predictor and demonstrated that preoperative osteopenia was an independent risk factor for poor OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 3 Higher PLR and NLR have been associated with poor survival in GC. 4 , 5 However, only a few studies have compared the effectiveness of multiple inflammatory response markers for predicting survival outcomes. In the current study, we identified the most suitable predictor and demonstrated that preoperative osteopenia was an independent risk factor for poor OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that in 324 patients with GC, an elevated preoperative GPS was associated with a shorter OS and DFS 3 . Higher PLR and NLR have been associated with poor survival in GC 4,5 . However, only a few studies have compared the effectiveness of multiple inflammatory response markers for predicting survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations